2017
DOI: 10.2334/josnusd.16-0805
|View full text |Cite
|
Sign up to set email alerts
|

Management of developmental enamel defects in the primary dentition

Abstract: This study attempted to identify appropriate materials for restoration of enamel defects in the primary dentition, which were classified by severity and region with the modified developmental defects of enamel index. To identify the most appropriate materials, we used restorative materials to protect teeth and evaluated clinical outcomes of restoration. Three materials were used for restoration or repair after dislodgement of restorations. Our findings in this case suggest that, because of its durability and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…DED are a series of anomalies in both the quality and amount of enamel and can affect tooth formation, hardness and coloring (Figure 13.1). The reported prevalence of DED ranges from 5.3 to 78.9% (Andrade et al, 2019;Oliveira et al, 2006;Wada et al, 2017;Wagner, 2016). Our research group (Buccae Geminae) has studied the prevalence of DED in 5-year-old preschoolers from Teresina, Brazil and found that 33.7% have DED (Andrade et al, 2019).…”
Section: Genetic Influence On Developmental Enamel Defectsmentioning
confidence: 94%
See 1 more Smart Citation
“…DED are a series of anomalies in both the quality and amount of enamel and can affect tooth formation, hardness and coloring (Figure 13.1). The reported prevalence of DED ranges from 5.3 to 78.9% (Andrade et al, 2019;Oliveira et al, 2006;Wada et al, 2017;Wagner, 2016). Our research group (Buccae Geminae) has studied the prevalence of DED in 5-year-old preschoolers from Teresina, Brazil and found that 33.7% have DED (Andrade et al, 2019).…”
Section: Genetic Influence On Developmental Enamel Defectsmentioning
confidence: 94%
“…Different varieties of enamel defects can occur, including enamel hypoplasia, caused by the reduction of enamel thickness that takes place during the secretory phase of amelogenesis. An imperfection in enamel translucence can occur if ameloblasts are damaged in the mineralization stage, a defect known as enamel hypomineralization (Andrade et al, 2019;Oliveira et al, 2006;Wada et al, 2017;Wagner, 2016).…”
Section: Genetic Influence On Developmental Enamel Defectsmentioning
confidence: 99%